If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27(k + -4) = 81 Reorder the terms: 27(-4 + k) = 81 (-4 * 27 + k * 27) = 81 (-108 + 27k) = 81 Solving -108 + 27k = 81 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '108' to each side of the equation. -108 + 108 + 27k = 81 + 108 Combine like terms: -108 + 108 = 0 0 + 27k = 81 + 108 27k = 81 + 108 Combine like terms: 81 + 108 = 189 27k = 189 Divide each side by '27'. k = 7 Simplifying k = 7
| 2x-8x-4=8 | | 27(k-4)=3 | | 27k+108=3 | | -9x=2(3x^2+4)+10x | | 2(p-1)-3(p-4)+12=4p | | 49a^2=16 | | .67x=400 | | 12b^2-13bv=3 | | 11-8x=119-29x | | 3(x-4)=-3(x-2) | | x^2+40x+224=0 | | 4x+3=11x-57 | | 4x-3=11x-57 | | 4(x-1)-2(x-5)=14 | | 15+3=1218 | | 7x-21=7 | | 19x^2-14=0 | | 4.33-3.5= | | 10x^2*3x^2= | | 41/3-31/2= | | 10x^2+3x^2= | | 0=x^4-4x^3 | | v-3.8=4.7 | | x+.07x=40.66 | | 4x+5=3y+2 | | 8x-6=5-2x | | (6x+7)(-8x-7)= | | t^2-6t=3 | | t^2-6t=p | | 3(4x-6)=3(4x+3) | | 3(4x-6)=3(4x-7) | | 3(4x-6)=3(4x-6) |